ANALISIS STRATEGI PEMASARAN WISATA SEJARAH (Rumah Bung Karno dan Rumah Fatmawati) DI KOTA BENGKULU - Sulisti Afriani; Neri Susanti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2017)
Sulisti Afriani dan Sulisti Afriani: The purpose of this study was to determine the SWOT analysis is applied to the marketing strategy in the House and the House Fatmawati Soekarno Bengkulu. Data collection methods used were a questionnaire method to distribute a list of questions to respondents. The analytical method used is the SWOT analysis to determine the internal factors (strengths and weaknesses) and external factors (opportunities and threats), which will then be incorporated into the SWOT matrix.The results of this study showed that factor analysis in the table "Opportunities" (Opportunity) has a total score of 0.925, while the factor of "Threat" (Treaths) has a total score of 1.206. From the data in the two tables, it is known that the total score of each factor can be specified that the factor of "Strength (Strength)" has a total score of 1,662 while the factors of weakness (Weakness) has a total score of 1,328. And the factor of "Opportunities" (Opportunity) has a total score of 0.925 while the threat factor "(Treaths) has a total score of 1.206. It is known the value of "Strength (Strength)" beyond the differences of weakness (Weakness) of (+) 0.334 where the value is obtained from 1.662 to 1.328, and the value of the "Opportunities" (Opportunity) under the value of Threat "(Treaths) difference (-) 0.281 where the value is obtained from 0.925 to 1.206. Cartesian diagram SWOT Analysis "Home and Home Fatmawati Soekarno Bengkulu city is in quadrant II, so the history of the travel marketing strategy at both historic sites are: pursuing a strategy of concentric diversification, pursuing a strategy to diversify horizontally and conduct of business strategy for the results.Key words: Marketing Strategy, SWOT